Review of once-monthly oral ibandronate and the use thereof - T De Villiers; M Davey; B Cassim; W De Lange (South African Family Practice)
An advisory board meeting of key opinion leaders was held in 2015 to discuss the clinical data on oral ibandronate in the treatment of postmenopausal osteoporosis.